2014
DOI: 10.1155/2014/507435
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effect ofZea maysL. (Purple Waxy Corn) on Experimental Diabetic Cataract

Abstract: Recently, substances possessing antioxidant can prevent cataractogenesis of diabetic cataract. Therefore, this study was carried out to determine the anticataract effect of Zea mays L. (purple waxy corn), a flavonoids rich plant, in experimental diabetic cataract. Enucleated rat lenses were incubated in artificial aqueous humor containing 55 mM glucose with various concentrations of Zea mays L. (purple waxy corn) ranging between 2, 10, and 50 mg/mL at room temperature for 72 h. At the end of the incubation per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 22 publications
1
26
0
Order By: Relevance
“…Supplementation of anthocyanins (50 mg/kg body weight) from the seed coat of black soybean to N-methyl-N-nitrosourea-induced retinal degenerative rats also prevents retinal degeneration [94], and also suppresses human lens epithelial cell death under hydrogen peroxide-induced oxidative stress by 50–200 μg/ml of the extract [93]. Anthocyanin also predominates around 70% in purple corn seed [124], where purple corn seed extract decreases lens opacity together with lower malonaldehyde levels [92]. …”
Section: Nutraceutical and Pharmaceutical Effects Of Anthocyaninsmentioning
confidence: 99%
“…Supplementation of anthocyanins (50 mg/kg body weight) from the seed coat of black soybean to N-methyl-N-nitrosourea-induced retinal degenerative rats also prevents retinal degeneration [94], and also suppresses human lens epithelial cell death under hydrogen peroxide-induced oxidative stress by 50–200 μg/ml of the extract [93]. Anthocyanin also predominates around 70% in purple corn seed [124], where purple corn seed extract decreases lens opacity together with lower malonaldehyde levels [92]. …”
Section: Nutraceutical and Pharmaceutical Effects Of Anthocyaninsmentioning
confidence: 99%
“…Epidemiological studies have demonstrated a relationship between the consumption of food with high quantities of phenolic compounds and a reduction in the risks of chronic and degenerative diseases, such as cancers and cardiovascular disease. Corn seed possesses antidiabetic, antioxidant, antiproliferative, and anti-cataractogenic activities [18,[39][40][41].…”
Section: Biological Activitiesmentioning
confidence: 99%
“…The toxicological assessment of corn at various doses against various clinical parameters has proven it clinically nontoxic and can be used for nutritional and medicinal purposes [53]. Anthocyanins in purple waxy corn have been reported to be effective against diabetic cataract [39]. Corn silk is usually discarded as waste and not used for nutritional purpose.…”
Section: Medicinal Importancementioning
confidence: 99%
“…Aldose reductase (AR) activity was assessed by using spectroscopy with the method of Thiraphatthanavong et al (2014) . Here DL‐glyceraldehyde was used as a substrate.…”
Section: Methodsmentioning
confidence: 99%